A study of the compressibility behavior of peat stabilized by DMM: lab model and FE analysis - Kim Huat, Bujang; Kazemian, Sina; Prasad, Arun; Barghchi, Maassoumeh (Academic Journals, 2011)
Peats are considered as extremely soft, unconsolidated deposits. These soils are geotechnically problematic, due to their high compressibility and low shear strength. Cement is widely used for the stabilization of peat by deep mixing method (DMM). This paper presents the results of the model study of compressibility properties of fibrous, hemic and sapric peats, stabilized with columns formed by DMM. The columns were formed of peat, treated with cement in different proportions. Rowe cell tests were performed after curing the samples for 28 days, to evaluate the compressibility characteristics. The results showed that the compressibility properties of peat can be improved significantly by the installation of cement stabilized columns. The amount of cement used to form the column and its diameter were observed to influence the engineering behavior of peats. The effect of cement was the highest on sapric peat among all, due to its physico-chemical properties. The results of Rowe cell were used to simulate the consolidation behavior using finite element software, PLAXIS and the results agree well. The parameters from the simulated model behavior were used to predict the ultimate bearing capacity of peat with full size cement stabilized columns.